Performance investigation of water-soluble additives for drag reduction agent in pipelines - Emsalem, Faraj Hawege (2016)
In the past few decades, several passive and active techniques to enhance the flow in pipelines have been suggested by scientists and implemented by the oil and gas industry. The most commercially feasible flow enhancement (drag reduction) technique is the injection of minute quantities of viscoelastic polymeric additives in the main flow stream. At the same time, this technique comes with a major disadvantage: the polymeric additives are resistant to the high shear forces exerted by the pumps and/or the turbulence inside the pipe. The present work addresses the said problem by proposing an alternative technique that involves the formation of polymer–surfactant complexes to create a highly shear-resistant additive through physical interaction with oppositely and similarly charged surfactants. Polyacrylic acid (PAA), Polyacrylamide-co-diallyl-dimethylammonium chloride P(AAm-co-DADMAC), hydroxypropyl cellulose (HPC), and polydiallyldimethylammoniumchloride (PDADMAC) polymers are adopted as drag-reducing agents (DRA). Sodium oleate and Tween 20 surfactants are also used as DRAs and complex creation agents. One of the major objectives of the present work is to prove that complexes can be formed even with similarly charged ingredients (i.e., polymers and surfactants). The experimental work is divided into three major phases. The first phase tests the flow behavior and shear resistance of the polymeric, surfactant, and complex DRAs using a rotating disk apparatus (RDA). The second phase detects the morphology of the formulated complexes using transmission electron microscopy (TEM) and cryo-TEM. The third phase conducts a pipeline drag reduction test using a closed-loop liquid circulation system, in which the pressure drop and flow rate measurements are taken to evaluate the drag reduction performance of a selected complex and its initial polymeric and surfactant substances. The RDA results show that, when tested at 700 ppm concentration and Re = 816650, all the polymeric additives have drag reduction potential with a maximum %DR of 16%, 32%, 40%, and 12% for PAA, P(AAm-co-DADMAC), HPC, and PDADMAC polymers, respectively. Moreover, when tested at 700 ppm concentration and Re = 816650, most of the surfactant additives show an acceptable drag reduction performance with a maximum %DR of 16% and 12% for sodium oleate and Tween 20 surfactants, respectively. The complexes created from the initial polymeric and surfactant additives significantly improve drag reduction performance and resistance to shear forces. The resistance of PAA is enhanced by 66% when tested at 500-ppm sodium oleate and Re = 489990. The resistance of PAA is massively enhanced by 203% when tested at 500-ppm sodium oleate and Re = 914648. The morphology of the formulated complexes is tested using TEM and cryo-TEM, and the results indicate that similarly charged polymer and surfactant molecules have the ability to form certain aggregates with the aid of the free counter ions in water. The TEM shows network-like aggregates that capture surfactant clusters in a network of polymers and small surfactant micelles. A similarly charged PAA–sodium oleate complex is tested in a pipeline system. The experimental results clearly indicate that the drag reduction performance of the polymers is massively improved by 51% when forming a complex with 1000-ppm concentration. In addition, the pressure drop reading results show that resistance to high-shear forces is highly modified when the complex is formed, and no detectable degradation is reported. It is believed that the same technique should be implemented using crude oil additives in the future due to the increasing need for such complexes in the oil and gas industry field.